Language Style Used in Novel œDilan: Dia adalah Dilanku (Tahun 1990) - Hartati, Hartati; Meisuri, Meisuri (Universitas Negeri Medan, 2021)
This study deals with the language styles used in œDilan: Dia adalah Dilanku Tahun 1990 novel by Pidi Baiq. The objectives of this study are to find out the types of language styles, the realization of the types, and the reason why the types of language styles used by the main character in the novel. The study was conducted by using by using descriptive qualitative method. The data were taken from Dilan™s utterances, as the main character, in the novel. The technique of collecting the data was transcribing the data from the novel and then eliminating the data to be analyzed. After analyzing the data, it was found that there were five types of language style used by Dilan with the consultative style for most contributing style (79,4%) of all usage, followed by casual style, formal style, frozen style, and intimate style.